2008
DOI: 10.1051/0004-6361:200810265
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic flux cancellation associated with a recurring solar jet observed withHinode,RHESSI, andSTEREO/EUVI

Abstract: Aims. We study the physical properties of a recurring solar active region jet observed in X-rays and extreme-ultraviolet (EUV). Methods. Multi-wavelength data from all three instruments on board Hinode were analysed. X-ray imaging and spectroscopy of the microflaring emission associated with the jets was performed with the Reuven Ramaty High Energy Spectroscopic Imager (RHESSI). Associated EUV jets were observed with the Sun Earth Connection Coronal and Heliospheric Investigation (SECCHI)/Extreme Ultraviolet I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 43 publications
7
82
0
Order By: Relevance
“…This type of V image has been used to analyse the dynamic motions of magnetic elements in the photosphere (Otsuji et al 2007). In a way similar to Chae et al (2007) and Chifor et al (2008), we use the ratio V/I to calculate the line-of-sight magnetic field B LOS in a sub-area around the reconnection site. This B LOS magnetogram is found to be consistent with the scaled V image, which is scaled to the MDI magnetogram, assuming that the magnetic flux observed by MDI is equal to that observed by SOT.…”
Section: Data Calibration and Alignmentmentioning
confidence: 99%
“…This type of V image has been used to analyse the dynamic motions of magnetic elements in the photosphere (Otsuji et al 2007). In a way similar to Chae et al (2007) and Chifor et al (2008), we use the ratio V/I to calculate the line-of-sight magnetic field B LOS in a sub-area around the reconnection site. This B LOS magnetogram is found to be consistent with the scaled V image, which is scaled to the MDI magnetogram, assuming that the magnetic flux observed by MDI is equal to that observed by SOT.…”
Section: Data Calibration and Alignmentmentioning
confidence: 99%
“…Several EUV jets repeatedly occurred in the active region where pre-existing magnetic flux was canceled by newly emerging flux of opposite polarity. Chifor et al (2008) analyzed a recurring solar active region jet that is observed in X-ray and EUV, finding a correlation between recurring magnetic cancellation and the X-ray jet emission. The jet emission was attributed to chromospheric evaporation flows due to recurring magnetic reconnection.…”
Section: Introductionmentioning
confidence: 99%
“…They have been observed in various wavelengths (X-ray, EUV and Hα) by the instruments on board Yohkoh, Stereo and Hinode satellites (Shimojo et al 1996;Chae et al 1999;Chifor et al 2008a;Patsourakos et al 2008). Jets may appear recurrently (Chifor et al 2008b) over bright points and strong flows are measured along their length. These bright points, which often are associated with microflaring activity, may correspond to emerging magnetic flux from below the photosphere (Canfield et al 1996).…”
Section: Introductionmentioning
confidence: 99%